THE EFFECT OF THINK-TALK-WRITE STRATEGY ON STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT - Cornelius Natanael Ambarita; Selviana Napitupulu; Leonita Maria Efipanias Manihuruk (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this researchwas to find out how the Think Talk Write (TTW) Strategy affects students' descriptive text writing skills, particularly with regard to generic structure. The research design used for this quantitative study was a quasi-experimental one. 397 students from SMA Negeri 3 Pematangsiantar's class X make up the sample population. The sample was chosen using purposeful sampling. The sample was divided into the experimental and control groups. A 34-student experimental class called Class X IPA 6 was taught using the Think Talk Write (TTW) Strategy. 34 students in Class X IPA 2 make up the control group, who receive traditional instruction. The instrument for gathering data was a writing test. The results of data analysis using the t-test formula showed that the t-test value was greater than the t-table value (t-test t-table = 2,5 1.668). The results show that while Ho is rejected, Ha is accepted. It is therefore possible to draw the conclusion that the Think Talk Write (TTW) strategy significantly affects students' capacity to write descriptive text.